Are Investors' Corporate Site Visits Informative? - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2013)
Corporate site visit is an important type of investors’ information acquisition activities, but its usefulness is not well understood in the literature, partially due to the lack of data. Using a unique dataset of corporate site visits in China, we analyze the information content and the determinants of corporate site visits. Our main findings are as follows. First, we document a significant market reaction to corporate site visits and the market reaction is stronger for group visits, for visits conducted by mutual fund managers, for visits covering firm-specific topics, and for firms with poorer information environment. Second, we find that stock returns around site visits are positively associated with forthcoming earnings news, suggesting that corporate site visits enable investors to obtain information predictive of future earnings. Lastly, consistent with the cost and benefit of conducting site visits, investors are more likely to conduct site visits to profitable firms, firms with more business segments, firms with a higher market share, and firms located closer to economic centers. Additional tests indicate that site visits represent selective access events, not selective disclosure events. Overall, our study contributes to the literature by presenting the first systematic evidence on the information role of corporate site visits.